KETERAMPILAN MEMBACA NYARING DENGAN MENGGUNAKAN MEDIA KARTU KATA - Fitriani Fitriani (IAIN Palopo, 2018)
This study aims to determine the increase in reading literacy skills by using word card media for grade II students of SDN 55 Padang Lambe, Wara Barat District, Palopo City. This research is a classroom action research (PTK) and the one acting as the subject in this study was the second grade students of SDN 55 Padang Lambe, Wara Barat Sub-district, Palopo City, totaling 15 people. Data collection techniques used through observation, tests and documentation methods with planning, implementation, observation and reflection procedures. This research was conducted in two cycles. Data processing and analysis techniques used are quantitative descriptive techniques. The results of this study using word cardmedia in increasing loud reading skills have increased, which can be seen in the average pre-cycle 67.66 with 33.33% completeness, in cycle I the average value is 72.6 with 80% completeness and in cycle II the average value was 83.46 with 100% completeness. Thus the average value of students has reached the KKM.